The Use of the Synergistic Approach When Conducting Studies In Biology (Journal of Educational Sciences, 2020)
The article deals with the application of synergetics in various sciences, including Biology. Synergyplays an important role in ensuring the development of the individual as a biological and intellectualsubject. Synergetics helps to understand the processes of self-organization of human activity, the orderingof his actions. Properties considered in synergetics-autonomy and self-regulation allows us to drawcertain parallels between cybernetic laws and the laws of synergetics.The synergetic approach, its ideas and main strategies can help autonomy, self-education of theindividual, development of personal qualities. Conducting classes in Biology using synergetic methodsis characterized by a variety of methods and their diversity, in contrast to traditional training andconducting classes. The authors are currently using the synergetic method when conducting severalclasses in Biology. In addition, synergetics has recently become one of the new interdisciplinaryresearch areas in science that are of interest to the educational and scientific community around theworld. It is provided an example in the article and summarizes the innovative experience of conductingBiology classes using a synergetic approach on the basis of gymnasium No. 176 in Almatyfor 8th grade students. The content of the classes included integrated sections of the renewed Biologyprogram.Key words: synergetics, pedagogy, natural sciences, educational process, traditional approach.